CDPKs and 14-3-3 Proteins: Emerging Duo in Signaling. (March 2017) - Ormancey, Mélanie; Thuleau, Patrice; Mazars, Christian; Cotelle, Valérie
Abstract : Calcium-dependent protein kinases (CDPKs) are Ca 2+ -sensors that play pivotal roles in plant development and stress responses. They have the unique ability to directly translate intracellular Ca 2+ signals into reversible phosphorylation events of diverse substrates which can mediate interactions with 14-3-3 proteins to modulate protein functions. Recent studies have revealed roles for the coordinated action of CDPKs and 14-3-3s in regulating diverse aspects of plant biology including metabolism, development, and stress responses. We review here the underlying interaction and cross-regulation of the two signaling proteins, and we discuss how this insight has led to the emerging concept of CDPK/14-3-3 signaling modules that could contribute to response specificity. Trends: Signaling events involving Ca 2+, protein phosphorylation, and protein–protein interactions are crucial mediators of plant responses to diverse endogenous and environmental cues. CDPKs are Ca 2+ sensor/kinase effector proteins that play key roles in plant development and stress responses. 14-3-3s are eukaryotic proteins regulating biological processes by phosphorylation-dependent protein–protein interactions. By interacting with a wide range of proteins, 14-3-3s play a prominent role in diverse aspects of plant physiology. Recent advances have demonstrated cross-regulation between CDPKs and 14-3-3s, and that they act in concert in plant signaling pathways.